Redescription of some poorly known species of Cytaea Keyserling, 1882 (Araneae: Salticidae), with new synonymies - Patoleta, Barbara M.; Trębicki, Łukasz (Zootaxa, 2015)
Eight nominal species of Cytaea were studied. The poorly known Cytaea fibula Berland, 1938, C. flavolineata Berland, 1938 and C. oreophila Simon, 1902 are redescribed, diagnosed and illustrated. Cytaea aeneomicans Simon, 1902 and C. guentheri Thorell, 1895 are synonymized with C. dispalans (Thorell, 1892), while C. whytei Prószyński & Deeleman-Reinhold, 2010 is synonymized with C. haematica Simon, 1902.